Customs And Everyday Life Of The Peoples Of Turkestan In The Late 19th Century (Texas Journal of Philology, Culture and History, 2026)
This topic explores the customs and everyday life of the peoples of Turkestan in the late 19th century. It examines social structure, family traditions, religious influence, economic activities, and cultural practices of different ethnic groups living in the region. Special attention is given to traditional occupations, housing, clothing, and rituals connected with important life events such as birth, marriage, and death. The study highlights how Islamic values and local traditions shaped the daily life and cultural identity of Turkestan’s population during this historical period.